2014
DOI: 10.1016/j.psychres.2014.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Clinical differences between cocaine-induced psychotic disorder and psychotic symptoms in cocaine-dependent patients

Abstract: Page 2 of 24The aim of this study is to compare the clinical characteristics of three groups of patients in treatment for cocaine dependence: patients without any psychotic symptoms (NS), patients with transient psychotic symptoms (PS) and patients with cocaine-induced psychotic disorder (CIPD). An observational and retrospective study of 150 cocaine-dependent patients undergoing treatment in the Drug Unit of the Psychiatry Department of University Hospital Vall d'Hebron in Barcelona (Spain) using these three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Also, in cocaine-dependent patients, aggression-hostility was associated with greater drug abuse and psychiatric severity [43]. Furthermore, CIP has been associated with agitated behavior and aggression [10], [12], [15], legal problems [20] and, in the same studies, with antisocial personality disorder [6], although this association is controversial [9], [23].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Also, in cocaine-dependent patients, aggression-hostility was associated with greater drug abuse and psychiatric severity [43]. Furthermore, CIP has been associated with agitated behavior and aggression [10], [12], [15], legal problems [20] and, in the same studies, with antisocial personality disorder [6], although this association is controversial [9], [23].…”
Section: Discussionmentioning
confidence: 94%
“…Although many risk factors of CIP in cocaine-dependent patients have been described, they have yet to be conclusively elaborated [18]. CIP has been associated with greater addiction severity [19], [20] agitated behavior, and aggression [12], [15]. Although assessment of personality during heavy drug use is complex, and there is some debate about its stability [16], [21], [22] antisocial personality disorder has been proposed as a risk factor for CIP [13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Chen et al [ 8 ] reported that individuals with methamphetamine-induced psychosis exhibited significantly more major depression than those without SIPD. On the other hand, Tang et al [ 29 ] and Roncero et al [ 4 ] did not find a significant difference in major depression between cocaine-dependent patients with and without SIPD. While we found no association between anxiodepressive symptoms and SIPD in the current study, we did find an association between anxiodepressive symptoms and self-reported psychotic symptoms in SUD individuals without SIPD.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, two previous studies reported no differences in alcohol or opioid dependence between SIPD patients and SUD patients without SIPD [ 11 , 29 ]. However, other studies examining cocaine-induced psychosis found that alcohol dependence was significantly elevated in SIPD patients, compared to individuals without SIPD [ 4 ]. The differences between studies in terms of alcohol dependence among patients with and without SIPD likely reflect baseline variations between cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation